GROUND GLASS OPACITIES ON CT OF THE CHEST IN THE PRACTICE OF THE CLINICIAN: PATHOGENESIS, SIGNIFICANCE, DIFFERENTIAL DIAGNOSE - M. A. Karnaushkina; A. V. Averyanov; V. N. Lesnyak (Архивъ внутренней медицины)
Ground glass opacities, mosaic perfusion, areas of air-trapping on a computed tomography of the lung are one of the most frequent x-ray syndromes. It`s are one of the kind of syndromes increase the density of pulmonary parenchyma. It is important to remember that the syndromes of ground glass opacities, mosaic perfusion, areas of air-trapping involve the differential diagnosis and not a diagnosis in itself. Differential diagnostic range very wide, since this syndrome commonly occurs in diseases that affect small bronchi, pulmonary vessels, alveoli and interstitial tissue. It is often observed a combination of lesions of various components of the pulmonary parenchyma. These combinations often help the doctor find the key to the correct diagnosis. Another problem in the evaluation of these syndromes are the distinction between pathological and “healthy” areas of lung tissue. Thus, in certain diseases, regions with higher density of the lung tissue may be normal lung parenchyma. The aim of this lecture is to analyze the reasons for the formation of the CT-types of ground glass opacities, mosaic perfusion, areas of air-trapping in norm and pathology, selection of distinctive features, allowing determining the elements of the lung parenchyma, the underlying pathological process, thereby narrowing the differential diagnosis of several diseases.